2019
DOI: 10.3390/e21010061
|View full text |Cite
|
Sign up to set email alerts
|

K-th Nearest Neighbor (KNN) Entropy Estimates of Complexity and Integration from Ongoing and Stimulus-Evoked Electroencephalographic (EEG) Recordings of the Human Brain

Abstract: Information-theoretic measures for quantifying multivariate statistical dependence have proven useful for the study of the unity and diversity of the human brain. Two such measures–integration, I(X), and interaction complexity, CI(X)–have been previously applied to electroencephalographic (EEG) signals recorded during ongoing wakeful brain states. Here, I(X) and CI(X) were computed for empirical and simulated visually-elicited alpha-range (8–13 Hz) EEG signals. Integration and complexity of evoked (stimulus-lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 95 publications
1
7
0
Order By: Relevance
“…Moreover, the resting EEG power spectrum is modulated according to whether an individual maintains the resting state with eyes open and closed. Most studies consistently find greater theta, alpha, and beta spectral power during eyes closed versus eyes open states [ 35 , 36 , 37 , 38 , 41 , 47 , 61 , 62 ], differences that in part reflect a transition from “cortical idling” in the absence of visual or cognitive stimulation to active perceptual and cognitive engagement [ 80 ]. We also observed this eyes closed versus eyes open activity pattern across both environments within all three frequency bands in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the resting EEG power spectrum is modulated according to whether an individual maintains the resting state with eyes open and closed. Most studies consistently find greater theta, alpha, and beta spectral power during eyes closed versus eyes open states [ 35 , 36 , 37 , 38 , 41 , 47 , 61 , 62 ], differences that in part reflect a transition from “cortical idling” in the absence of visual or cognitive stimulation to active perceptual and cognitive engagement [ 80 ]. We also observed this eyes closed versus eyes open activity pattern across both environments within all three frequency bands in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…We chose studies to include in the meta-analysis according to the following criteria: (1) a study utilized a resting state task, an arithmetic task, and/or the PASAT, (2) a study used a repeated-measures contrast to compare EEG power across experimental variables similar to the present study (resting task: eyes open versus eyes closed; PASAT: arithmetic performance versus rest or similar control condition); and (3) a study explicitly reported the information necessary to compute effect size (means, standard deviations/errors, and/or values of inferential statistics). Using these criteria, we identified 7 studies using the resting task, with 4 of these studies measuring theta and beta power [ 37 , 47 , 61 , 62 ], and all 7 studies measuring alpha power [ 35 , 36 , 37 , 38 , 47 , 61 , 62 ]. We also identified 9 studies using an arithmetic task or the PASAT, with 5 of these studies measuring theta power [ 63 , 64 , 65 , 66 , 67 ], 7 measuring alpha power [ 63 , 64 , 65 , 67 , 68 , 69 , 70 ], and 3 studies measuring beta power [ 66 , 69 , 71 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plenty of them are time-frequency analysis, with the use of tools such as wavelets or matching pursuit [7, 8, 17, 22, 25, 47, 49]. Some of them are fractal or entropy based [45, 51]. Others use the independent component analysis and similar techniques [26, 3, 44, 23].…”
Section: Introductionmentioning
confidence: 99%